Processing of Psenes indicus, Decapterus sp. and Stolephorus sp. to Dried Product with Low Histamine and their Storage Characteristics - R., Chakrabarti (Fishery Technology, 2025)
Traditional dried products like whole sundried Stolephorus sp., whole salted sundried Psenes indicus and Decapterus sp. were found to contain frequently high levels of histamine in muscle. An attempt was made to reduce histamine level in these fish by using suitable processing techniques. lt was found that histamine in whole unsalted sun dried fish > gutted unsalted sundried fish > whole salted sundried fish > gutted salted sundried fish. During storage at ambient temperatures (30Â±Â 10Â°C), histamine levels showed deaeasing trends in case of dried P. indicus and Stolephorus sp., but was irregular in case of dried Decapterus sp.; TVBN showed increasing trend in all dried fish during the same period.